External debt and economic growth: A study from the perspective of developing and emerging economies - Abbas , Shehzada Ghulam (Asian Journal of Economics and Empirical Research, 2024)
This study explores the relationship between economic growth and external debt for 24 highly indebted developing and 21 highly indebted emerging economies. This study uses data from 2010 to 2019 and a dynamic panel data model-Generalize Methods of Moments (GMM) to investigate the relationship. The study found that external debt significantly and adversely impacts economic growth for the sample of 24 developing countries indicating external debt being one of the major determinants of economic growth for developing countries whereas it is negative but insignificant in the case of 21 emerging economies showing no impact of external debt on economic growth in the case of emerging economies. This study also found a significant and positive relationship between gross capital formation (GCF) and lag of GDP growth (GDPgr) and economic growth for both developing and emerging economies. Inflation has no significant impact on economic growth in the case of developing countries whereas it has a significant and negative impact on economic growth for the sample of emerging economies. Trade openness has no significant impact on economic growth for data samples. In addition, the long-run estimates show a negative relationship between external debt and GDP growth for both groups of countries. The results imply that targeted and efficient debt management and using traditional alternatives (i.e., tax revenue mobilization and domestic borrowing) should be prioritized for both countries.